HIDRADENITIS SUPPURATIVA AND DIABETES MELLITUS: A SYSTEMATIC REVIEW - Jani Sari Dabukke, Yeyen (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Objective: Hidradenitis suppurativa (HS), also known as acne inversus is a persistent inflammatory skin disease. This condition causes lesions such as deep-seated nodules and abscesses, draining tracts, and fibrotic scars. Preliminary data indicates a possible biological connection between diabetes mellitus (DM) and HS. This study aimed to review the correlation between hidradenitis suppurative and diabetes mellitus systematically.Materials and methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, ProQuest) and included articles published between 2019–2023. Duplicate publications, review articles, and incomplete articles were excludedResults: Database search yielded 214 articles, which were systematically eliminated, leaving 5 relevant articles. Analyzed articles showed the association between diabetes mellitus and hidradenitis suppurativa.Conclusion: Studies support a significant relationship between HS and DM. Although the prevalence was variative, the association between the two conditions was significant.